2003
DOI: 10.1046/j.1365-4362.2003.01796.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Kasabach–Merritt syndrome: a stepwise regimen of prednisolone, dipyridamole, and interferon

Abstract: KMS may be treated in a stepwise approach. High-dose steroid does not result in a high response rate and is not tolerated well. The response to IFNalpha2b is more favorable, but life-threatening adverse events may occur. Chemotherapy with vincristine or vinblastine may be useful as adjunctive therapy in KMS, but experience is still limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 25 publications
0
38
0
11
Order By: Relevance
“…Rather than concurrent treatment, more number of authors of published literature suggests use of sequential approach with various modalities for KMS [23,24]. The general approach is to manage coagulopathy effectively with supportive care and medical management [23][24][25][26][27][28][29][30] …”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than concurrent treatment, more number of authors of published literature suggests use of sequential approach with various modalities for KMS [23,24]. The general approach is to manage coagulopathy effectively with supportive care and medical management [23][24][25][26][27][28][29][30] …”
Section: Managementmentioning
confidence: 99%
“…The general approach is to manage coagulopathy effectively with supportive care and medical management [23][24][25][26][27][28][29][30] …”
Section: Managementmentioning
confidence: 99%
“…One study demonstrated that treatment with prednisolone at 2 or 3 mg/kg/day achieved response in 30% to 72% of infants 16 . However, other data suggested variable response to prednisolone, ranging from no efficacy to significant regression in lesion size, and even complete remission 7 . The discrepant results may be due to variation in patient clinical characteristics in the studies, such as different pre-existing tumors, and the possibility that the enrolled patients actually had vascular malformations, rather than hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is another option which can induce embolization within the hemangiomas. These options are usually recommended as second-line therapies 6,7,15 . However, treatment with these regimens can result in severe adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation